Hubungan Persepsi Iklim Organisasi dan Dukungan Organisasi dengan Organizational Citizenship Behavior pada Aparatur Sipil Negara di Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Medan - Abdi Hardiansah Hasibuan; Risyda Fadilah; Hasanuddin Hasanuddin (Mahesa Research Center, 2022)
This study aims to see: The relationship between perceptions of organizational climate and organizational support for Organizational Citizenship Behavior (OCB) in ASN at the Center for the Development and Empowerment of Educators and Education Personnel (P4TK) Medan. This research was conducted on 150 ASN with total sampling technique. The results showed; 1. There is a very significant positive relationship between the perception of organizational climate and organizational support for Organizational Citizenship Behavior (OCB) at the State Civil Apparatus at the Center for the Development of Quality Assurance for Vocational Education (BBPPMPV) BBL Medan. 2. There is a very significant positive relationship between the perception of organizational climate and Organizational Citizenship Behavior (OCB) in the State Civil Apparatus, Center for the Development of Quality Assurance for Vocational Education (BBPPMPV) BBL Medan. 3. There is a significant positive relationship between organizational support and Organizational Citizenship Behavior (OCB), with a correlation coefficient of rx2y = 0.431; p < 0.001; and the effective contribution obtained was 18.6%. The total effective contribution of the two independent variables (perception of organizational climate and organizational support) on Organizational citizenship behavior (OCB) is 48.3%. From these results it is known that there are still 51.7% of the influence of other factors on Organizational Citizenship Behavior (OCB) which was not seen in this study.